Identification and characterization of the metabolites of moscatilin in mouse, rat, dog, monkey and human hepatocytes by LC–Orbitrap–MS/MS combined with diagnostic fragment ions and accurate mass measurements. (26th December 2022) - Hu, Aizhen; Liu, Qingwang; Ouyang, Jing
Abstract: Moscatilin, a bibenzyl derivative from the stem of Dendrobium loddigesii, has been shown to have anticancer activity. The aim of this study was to identify and characterize the possible in vitro metabolites of moscatilin generated from hepatocytes. The metabolites generated in the hepatocytes of mouse, rat, dog, monkey and human were identified and characterized employing ultra‐high‐performance liquid chromatography coupled with quadrupole Orbitrap tandem mass spectrometry (LC–Orbitrap–MS/MS) based on diagnostic fragment ions and accurate mass measurements. A total of 18 metabolites were identified, among which seven were phase I and 11 were phase II metabolites. The plausible structures of the metabolites and the probable biotransformation pathways were proposed based on the diagnostic fragment ions, chemical formula and mass fragmentation pattern, as well as the accurate masses. The majority of phase I metabolites were generated by demethylation and hydroxylation, while phase II metabolites were mainly generated by glucuronidation, glutathione conjugation and sulfation. Our study first expounded the metabolites of moscatilin in mouse, rat, dog, monkey and human hepatocytes and provided a foundation for a further pharmacokinetic and toxicity study. More importantly, LC–Orbitrap–MS/MS combined with diagnostic fragment ions and accurate mass measurements has been proved to be an effective method for the rapid identification of bibenzyl derivatives and their metabolites.